Synthesis and Antiplasmodial Activity of 2-(4-Methoxyphenyl)-4-Phenyl-1,10- Phenanthroline Derivative Compounds - Hadanu, Ruslin; Mustofa, Mustofa; Nazudin, Nazudin (UI Scholars Hub, 2012)
A unique of synthetic methods was employed to prepare 2-(4-methoxyphenyl)-4-phenyl-1,10-phenanthroline (5) derivatives from 4-methoxy-benzaldehyde (1), acetophenone (2), and 8-aminoquinoline (4) with aldol condensation and cyclization reactions. The derivatives were tested through antiplasmodial test. The synthesis of derivatives compound 5 was conducted in three steps. The 3-(4-methoxyphenyl)-1-phenylpropenone 3 was synthesized through aldol condensation of 1 and 2 which has a yield of 96.42%. The compound 5 was synthesized through cyclization of compound 4 and 3 with 84.55% yield. The derivative of compound 5 was synthesized from compound 5 using DMS and DES reagents which refluxed for 21 and 22 h, to produce (1)-N-methyl-9-(4-methoxyphenyl)-7-phenyl-1,10- phenanthrolinium sulfate (6) and (1)-N-ethyl-9-(4-methoxyphenyl)-7-phenyl-1,10-phenanthrolinium sulfate (7) with 91.42 and 86.36% yields, respectively. Results of in vitro testing of antiplasmodial activity of compound 5 derivatives (i.e., compound 6 and 7) against chloroquine-resistant P. falciparum FCR3 strain showed that compound 7 had higher antimalarial activity than compounds 5 and 6. Whereas, results of in vitro testing against chloroquine-sensitive P. falciparum D10 strain showed that compound 6 has higher antimalarial activity than compounds 5 and 7.